Implementasi Penjaminan Mutu Internal Dalam Pengembangan Kurikulum Berbasis OBE - Sutrisna, I Putu Gede; Putrayasa, Ida Bagus; Wisudariani, Ni Made Rai; Sudiana, I Nyoman (Jayapangus Press, 2024)
Quality assurance is needed to improve quality in performing the education. The curriculum is the soul in implementing the education. The OBE-based curriculum emphasizes the quality of outcomes produced by the education. Therefore, an in-depth study is needed to determine the implementation of internal quality assurance in OBE-based curriculum development. The aim of this research was to describe the implementation of internal quality assurance in OBE-based curriculum development. To achieve this goal, this research used a qualitative descriptive approach with a content analysis method. The documents which were analyzed were Permendikbudristek 53 in 2024 and the Guide to Preparing the Higher Education Curriculum (KPT) in 2024. The data analysis technique used was an interactive analysis model. The result showed that the implementation of internal quality assurance in OBE curriculum development applied in the PPEPP cycle, namely Curriculum Determination (P), Curriculum Implementation (P), Curriculum Evaluation (E), Curriculum Control (P), and Curriculum Improvement (P).